Sensory Integration and Perceptual-Motor Profiles in School-Aged Children with Autistic Spectrum Disorder - Wuang YP (Dove Medical Press, 2020)
Yee-Pay Wuang,1 Chien-Ling Huang,2 Hsien-Yu Tsai1 1Department of Occupational Therapy, Kaohsiung Medical University, Kaohsiung, Taiwan; 2Department of Rehabilitation Medicine, Kaohsiung Medical University Chung-Ho Memorial Hospital, Kaohsiung, TaiwanCorrespondence: Yee-Pay WuangDepartment of Occupational Therapy, Kaohsiung Medical University, 100 Shih-Chuan 1st Road, Kaohsiung, TaiwanTel +11-886-7-3121101 ext2658Fax +11-886-7-3215845Email yeepwu@kmu.edu.twPurpose: This study aimed to investigate the sensory integration and perceptual-motor performances in elementary school children (5– 12 years) with autistic spectrum disorder (ASD) in Taiwan. The impacts of comprehensive body functions on activity participations in ASD were also investigated to provide evidence for clinical applications and further study.Methods: One hundred and seventeen children with ASD (42 females; aged 5– 13 years, average age 8 years 3 months) were recruited. All participants were assessed with standardized measures of body functions and activity participations. The body function measures included Bruininks–Oseretsky of Motor Proﬁciency – Second Edition, Sensory Proﬁle, Test of Sensory Integration Functions, and Test of Visual Perception Skills – Third Edition. The activity participation measures included the Chinese versions of both Vineland Adaptive Behavior Scale and School Function Assessment.Results: School-aged children with ASD had different levels of impairments on body function measures. Most participant scores fell within the impairment range on 13 to 15 items out of the total 19 sensory and perceptual-motor measure subtests, with worst performance on coordination-related motor task and most sensory integrative dimensions. The results indicated a significant main effect for age and sex on some body functions and activity participations. Correlation analyses indicated strong associations between body function and activity participation across settings in ASD.Conclusion: Our ﬁndings characterized the developmental continuum of body functions of school-aged children with ASD and showed their associations with adaptation and participation. While emphasizing the development of functional skills to facilitate age-appropriate activity participation in multiple scenarios, interventions aiming to improve body functions are indispensable.Keywords: ASD, motor function, sensory processing, sensory integration, visual perception, activity participation